Beyond the Smog: Unveiling the Invisible Toll of Air Pollution on the People's Mental Well‐Being in Lahore, Pakistan - Sidra Irfan; Muhammad Muzzamil; Nusrat Tahira; Beenish Altaf; Farwa Fatima; Abdullah Malikzai (Health Science Reports)
ABSTRACT Background The manuscript investigates the significant detrimental impact of air pollution, particularly smog, on the mental health of residents in Lahore, Pakistan. Research highlights various ways in which pollutants contribute to mental health issues, including increased risks of depression and anxiety, and direct impacts on cognitive function. Aims This study aims to establish a link between air quality and its psychological impact on the inhabitants of Lahore. It seeks to advocate for effective interventions to mitigate the adverse effects of air pollution on mental health. Methods This study examined existing literature on the Internet to understand the link between air pollution and mental health. This manuscript aimed to provide a foundation for developing evidence‐based solutions within the current healthcare landscape. Results Searching for “smog,” “mental health,” and “air pollution” yielded these results, a strong association between increasing levels of air pollution in Lahore and its impact on residents' mental well‐being. Despite ongoing efforts to mitigate air pollution, the persistent smog burden in Lahore highlights the need for more effective and decisive interventions to improve air quality and safeguard the population's mental health. Conclusion This study serves as a preliminary investigation into the intricate relationship between air pollution and mental health. It emphasizes the need for further research to comprehensively understand this critical issue and proper policy implications and potential interventions are required to mitigate the adverse effects of air pollution on mental health.